Banka dışı finansal kurumlar ve muhasebe uygulamalar - Yilmaz, Önder (My University, 2017)
Finansal araçların arz ve talebinin karşılaştığı finansal piyasalar ekonomikbirimler arasındaki ilişkinin en verimli ve etkin bir şekilde karşılanabilmesi için organizeolmaktadır.

Financial markets, where supply of and demand for financial instruments meeteach other are organized in such a way that the relationship among economic agents ismet in most effectively and efficiently. In this framework, depending on special featuresof each country, in some countries financial markets are dominated by capital markets,while in some others, including Turkey, banking sector has a significant role in thefinancial markets. Besides, factoring, leasing and financing institutions, also called asnon-bank financial institutions, contribute to the healthy functioning of the financialsystem by establishing a close relationship with their customers.
Keywords: Banka Dışı Finansal Kurumlar Financial markets; Bankalar ve bankacılık; Finansal piyasalar; non-bank financial institutions; Türkiye